Towards a Regime of Authenticity. Reading A Room with a View through the Lens of Contemporary Romance Scholarship - Francesca Pierini (Lea)
Through an analysis of E.M. Forster’s A Room with A View (1908), this article sets itself the twofold aim of (1) shedding light on the changes in courtship and the choosing of a partner that have characterised personal and romantic relationships over the last century, and (2) exploring an instance of the literary construction of Italian otherness in Anglophone fiction. By analysing the novel in the light of several recent insights and findings in (literary/popular) romance scholarship (Regis 2003; Fletcher 2008; Illouz 2012), this article corroborates the affiliations of A Room with a View with the romantic literary tradition.